A DEIXIS ANALYSIS OF SONG LYRIC IN ADELE “SOMEONE LIKE YOU” - Dina Karlina; Acep Haryudin (IKIP Siliwangi, 2021)
The aims of this research is to analyze the types of deixis and the dominant deixis in song lyrics “Someone Like You” by Adele. The discussion began by taking the lyric “Someone Like You” as the the data. This Research use qualitative as the method of the research for analysis the data. The researcher found 42 deixis in this song include the types of deixis. There are are: 36 case or (86%) of The Person deixis, 3 case or (7%) of The Spatial deixis, and 3 case or (7%) of The Temporal deixis. The result indicate that in “Someone Like you” the most dominant deixis is Person Deixis and followed by Spatial Deixis and Temporal Deixis which have same percentage. Keywords: Analysis, Deixis, Song